Evaluasi Pembelajar Kosakata dalam Meningkatkan Kemampuan Berbahasa Pembelajar BIPA - Azmi Fauziah; Abdul Azis (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to evaluate vocabulary learning in improving the language proficiency of Indonesian for Foreign Speakers (BIPA) learners. The research employed a descriptive qualitative approach, with data collected through observations, interviews, and documentation. Data were analyzed through data reduction, data display, and conclusion drawing. The findings reveal that systematic and varied vocabulary learning evaluations, including written tests, oral tests, and task-based assessments, effectively improve learners’ vocabulary mastery. In addition, continuous feedback helps learners correct language errors and enhance both receptive and productive language skills. Therefore, vocabulary learning evaluation plays an important role in supporting the improvement of BIPA learners’ language proficiency. This study recommends that BIPA instructors develop more varied, contextual, and continuous vocabulary evaluation models to support optimal learning outcomes